Patients preference for mode of delivery in a Middle Eastern society: a cross-sectional study - Aldardeir, Nashwa; Sulaimani, Mohammed; Bahowarth, Sarah Y.; Abdulaziz, Aseel H.; Alghalayini, Firyal K.; Halabi, Khloud W.; Alyazidi, Anas S.; Jastanieh, Eman S.; Alharbi, Raghad; Alamoudi, Shahad T.; Alrumaihi, Meshari; Malibary, Mohammed A. (Frontiers in Medicine, 2025)
BackgroundCesarean section (CS) rates are increasing globally, including in the Middle East. While CS can be a lifesaving procedure, unnecessary CS can lead to complications for both mother and child. Understanding factors influencing women’s delivery preferences is crucial for optimizing maternal and child health outcomes.MethodsThis cross-sectional study investigated factors influencing the preferred mode of delivery among 661 pregnant women in Jeddah, Saudi Arabia. Data were collected using a structured questionnaire and analyzed using descriptive statistics and logistic regression.ResultsMultiple factors showed significant associations with CS preference in multivariable analysis. Non-Saudi women had substantially higher odds of preferring CS compared to Saudi nationals (aOR 2.45, 95% CI 1.30–4.60). Urban residency (aOR 2.89, 95% CI 1.45–5.78) and higher income ≥50,000 SAR (aOR 4.15, 95% CI 1.02–16.88) were also strong predictors. Conversely, women aged 31–40 years had significantly lower odds of preferring CS (aOR 0.23, 95% CI 0.07–0.78) compared to those aged 18–24. Women with no prior CS were more likely to prefer spontaneous vaginal delivery, and previous CS in private hospitals significantly increased CS preference for subsequent deliveries.ConclusionThis study highlights the complex interplay of demographic, socioeconomic, and personal factors influencing women’s delivery preferences. Understanding these factors is crucial for developing targeted interventions to promote informed decision-making and optimize maternal and child health outcomes. Further research is needed to investigate the underlying reasons for these preferences.